2018
DOI: 10.1111/rode.12543
|View full text |Cite
|
Sign up to set email alerts
|

Structural transformation and its relevance for economic growth in Sub‐Saharan Africa

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…Since the McMillan et al (2014) striking finding that in many Latin American and Sub-Saharan African countries the broad patterns of structural change between 1990-2000 have served to reduce rather than increase economic growth, there has been a growing interest in SSA specific studies of structural transformation. Busse et al (2019) find that although the agricultural sector is still dominant, a structural transformation has taken place and that it has significantly contributed to African growth in the period 1980-2014. Busse et al (2019) use a two-sector model of agriculture and non-agriculture without distinguishing between the industrial and service sectors, and they do not account for the non-classical nature of structural change unfolding in SSA.…”
Section: Literature Reviewmentioning
confidence: 97%
See 2 more Smart Citations
“…Since the McMillan et al (2014) striking finding that in many Latin American and Sub-Saharan African countries the broad patterns of structural change between 1990-2000 have served to reduce rather than increase economic growth, there has been a growing interest in SSA specific studies of structural transformation. Busse et al (2019) find that although the agricultural sector is still dominant, a structural transformation has taken place and that it has significantly contributed to African growth in the period 1980-2014. Busse et al (2019) use a two-sector model of agriculture and non-agriculture without distinguishing between the industrial and service sectors, and they do not account for the non-classical nature of structural change unfolding in SSA.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Busse et al (2019) find that although the agricultural sector is still dominant, a structural transformation has taken place and that it has significantly contributed to African growth in the period 1980-2014. Busse et al (2019) use a two-sector model of agriculture and non-agriculture without distinguishing between the industrial and service sectors, and they do not account for the non-classical nature of structural change unfolding in SSA. Studying the Tanzanian economy, Diao et al (2018) find that although employment in the formal sector has increased, the bulk of growth is accounted for by firms in the informal sector.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Wells and Thirwall (2003) tested all three of Kaldor’s growth laws for contemporary African economies and found that, despite the rising importance of the services sector, the aggregate growth of GDP is overwhelmingly attributable to the growth of the manufacturing value added. In a recent panel analysis Busse, Erdogan, and Mühlen (2018) try to disentangle the sources of economic growth in 41 sub‐Saharan African countries over the period 1980–2014 and show that structural change contributes significantly to economic growth in the region. Hence, despite the discussion on the waning star of the manufacturing sector as the leading sector, it is still more than justified to conceptualize modern manufacturing as the driver of economic modernization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some scholars maintain that agriculture can play an important role in economic growth and the reduction of poverty. Busse et al (2018) explained the role of structural transformation in economic growth in sub-Saharan Africa, by estimating the overall productivity of the economy from productivities of different sectors. The results showed that although agriculture continues to employ a majority of the workforce, structural transformation has taken place in the continent and significantly contributed to economic growth.…”
Section: Review Of Literaturementioning
confidence: 99%